BETWEEN COLLOQUIAL SAYING, LITERARY IMAGES AND DIALOGUES. AN APPROACH TO LATE COLONIAL RIVER PLATE´S LANGUAGE - Mallo, Silvia C. (Revista de Historia Social y de las Mentalidades, 2011)
A different kind of use of Río de la Plata Justice papers is proposed here. It doesn’t concerns methodological or technical analysis of literary discourse and refers to observe words o literature constructions and dialogs as they are reproduced by the mediation of justice officers who perceives litigants and witnesses characteristics